Knowledge engineering and the semantic web : 4th International Conference, KESW 2013, St. Petersburg, Russia, October 7-9, 2013. Proceedings - Mouromtsev, Dmitry; Klinov, Pavel (Communications in Computer and Information Science, 2013)
This book constitutes the refereed proceedings of the 4th Conference on Knowledge Engineering and the Semantic Web, KESW 2013, held in St. Petersburg, Russia, in October 2013. The 18 revised full papers presented together with 7 short system descriptions were carefully reviewed and selected from 52 submissions. The papers address research issues related to knowledge representation, semantic web, and linked data.